Sperm mitochondrial membrane potential and motility pattern in the Holstein bull semen positive for heparin binding proteins - KRISHNAN, G; THANGVEL, A; LOGANATHASAMY, K; VEERAPANDIAN, C; KUMARASAMY, P; KARUNAKARAN, M (The Indian Journal of Animal Sciences, 2016)
Present study was aimed to evaluate sperm motility and mitochondrial membrane potential (MMP) in relation to the presence of heparin binding proteins (HBPs) in semen. Semen was collected from 17 Holstein Friesian breeding bulls. Seminal plasma and sperm membrane proteins were isolated by precipitation method; HBPs were isolated using heparin-sepharose affinity chromatography. SDS-PAGE was performed and bulls were categorized into 3 groups based on presence/absence of 24 and 30 kDa HBPs. Computer-assisted semen analysis revealed that fresh ejaculates of bulls positive for 30 kDa HBP had 4.24 and 14.18% of higher total motile sperm than semen with 24 kDa and negative for HBPs. Semen with 30 and 24 kDa had 18.72 and 12.34% of higher number of sperm with progressive motility and velocity than semen devoid of HBPs. Simultaneous assessment of plasma membrane integrity (PMI) and MMP by fluorescence staining revealed that post-thaw sperm of semen with 30 kDa HBP had 6.28 and 12.79% of higher intact PMI. Further, sperm of semen with 30 kDa HBP had 4.61 and 10.50% of higher MMP, which had travelled an extra distance of 9.71 and 4.95 mm through cervical mucus than semen with 24 kDa and devoid of HBPs. The mucus penetration distance showed a strong positive correlation with high MMP, PMI, sperm motility and velocity. It is to be concluded that HBPs were able to sustain higher percentage of motile sperm with progressive motility and MMP which was depicted by more mucus penetration distance.